SOSIALISASI PERAN AKUNTANSI DALAM PERSPEKTIF PETANI DI DESA NGAMPRAH KABUPATEN BANDUNG BARAT - Fatimah Nurjannati Iskandar (Jurnal Ekonomi dan Bisnis, 2024)
The success of the agribusiness sector in improving the Indonesian economy is because the operational activities of the agribusiness sector have a smaller level of risk. The Indonesian government continues to strive to increase people's income through developing the agribusiness sector by continuing to encourage increased production and downstream national agriculture. However, efforts to improve the agribusiness sector do not escape the capital and marketing problems that farmers continue to face. Capital for every business is the foundation for the establishment of a business. The problem with capital in farming is that it is difficult for farmers to understand accounting in agriculture and many farmers, especially village farmers, often ignore the importance of financial records in the running of their farming business. Based on this, the majority of human resources in West Bandung Regency are farmers who are superior in the field of agriculture, but there are weaknesses in achieving an understanding of financial recording in the business world because it appears that farmers are more focused on cultivating rice fields to produce good production and ignoring proper recording. with the applicable provisions in accounting. This program aims to improve the competency and skills of farmers in West Bandung regarding financial records in accordance with applicable regulations. This activity was prepared from answers to problems that occurred related to recording farmers' finances. The stages used in this service are Preparation, Implementation and Evaluation. The expected final result is an increase in bookkeeping knowledge and an increase in the income of farmers in West Bandung Regency.